Characteristics of MDS patients seen at private practices differ significantly from those treated at university hospitals in Germany - Nolte, Florian; Schumann, Christiane; Klein, Stefan; Reinwald, Mark; Hofmann, Wolf-Karsten (Journal of cancer research and clinical oncology, 2012)
Background: Myelodysplastic syndromes (MDS) are mainly a disease of the elderly. Commonly, MDS patients are treated in an outpatient setting making hematological/oncological private practices (PP) an important backbone in the management of MDS patients. Methods: To gain more insights into the characteristics of patients with MDS treated in hematological/oncological PP and to evaluate the daily diagnostic routines and classification systems used, we performed questionnaire-based analyses. Moreover, to investigate whether characteristics of MDS in PP differ from patients treated in specialized MDS centers in university hospitals (UH), we compared both cohorts of MDS patients.
Gesehen am 22.08.2018